2012
DOI: 10.1586/erm.12.40
|View full text |Cite
|
Sign up to set email alerts
|

The clinical utility of molecular karyotyping using high-resolution array-comparative genomic hybridization

Abstract: Clinical characteristics of patients are not always related to specific syndromes. Array-comparative genomic hybridization (aCGH) is used to detect submicroscopic copy number variants within the genome not visible by conventional karyotyping. The clinical application of aCGH has helped the genetic diagnosis of patients with unexplained developmental delay/intellectual disability, autism spectrum disorders, with or without multiple congenital anomalies. Since 2008, we have implemented aCGH with the 244K and 4 ×… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 53 publications
1
7
0
2
Order By: Relevance
“…In 14 patients, we identified known microdeletion and microduplication syndromes: DiGeorge (3), 1p36 microdeletion (3), 9q subtelomeric microduplication (3), Williams syndrome (2), CHARGE (Coloboma of the eye, Heart defects, Atresia of the choanae, Retardation of growth and/or development, Genital defect, Ear anomalies and/or deafness) (1), 17q21-31 microduplication (1), and Jacobsen syndrome (1) (Figure 1). In general, it is given that phenotypes of microduplications are milder as compared with those caused by microdeletions in the same chromosomal region; this was confirmed by our cases and previously published results (6).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In 14 patients, we identified known microdeletion and microduplication syndromes: DiGeorge (3), 1p36 microdeletion (3), 9q subtelomeric microduplication (3), Williams syndrome (2), CHARGE (Coloboma of the eye, Heart defects, Atresia of the choanae, Retardation of growth and/or development, Genital defect, Ear anomalies and/or deafness) (1), 17q21-31 microduplication (1), and Jacobsen syndrome (1) (Figure 1). In general, it is given that phenotypes of microduplications are milder as compared with those caused by microdeletions in the same chromosomal region; this was confirmed by our cases and previously published results (6).…”
Section: Discussionsupporting
confidence: 91%
“…The types of heart defect in each of the 37 patients with a pathogenic CNV detected are shown in Table 1. The assignment of CNVs pathogenicity was based on the gene content according to the University of California Santa Cruz Genome Browser database (http://genome.ucsc.edu/) human genome build 18 or 19 (6). In addition, these patients presented Congenital heart disease and array CGH Articles …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that JAKMIP1 was differentially expressed in patients with two syndromic forms of ASD, Fragile X and (dup)15q11–13 syndrome, and upon RBFOX1 knockdown (Fogel et al, 2012; Nishimura et al, 2007). To date, eleven ASD subjects have been identified with copy number variations that contain JAKMIP1 (Autism Genome Project et al, 2007; Kaminsky et al, 2011; Poultney et al, 2013; Tzetis et al, 2012). But, its interactions or function in the CNS, especially during brain development, are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…High resolution 4x180K and 1x244K Agilent SurePrint G3 arrays (>170.000 and >236.000 probes respectively, average resolution >8.9Kb) were used in this study (Agilent Technologies, Santa Clara, CA, www.agilent.com). Labeling, hybridization and data processing was carried out according to the manufacturer's recommendations and as previously described (3). The benign CNVs (or CNPs) that are reported in the Database for Genomic Variants (http://dgv.tcag.ca/dgv/app/home) were removed from the results.…”
Section: αRray-cgh Analysismentioning
confidence: 99%